Modeling and simulation of skyhook controller for active suspension system - Mohd Azee, Zaidee Ee (2010)
This paper presents modeling and simulation force tracking control of a hydraulic actuator applied in a quarter car of the active suspension system using skyhook control system. The controller structure of the active suspension system was decomposed into two loops namely outer loop and inner loop controllers. Outer loop controller is used to calculate the optimum target force to reject the effects of road disturbances by using skyhook control and proportional-integral-derivative (PID) control system, while, the inner loop controller is used to keep the actual force close to this desired force. The results of the study show that the inner loop controller is able to track well the target force ranging from sinusoidal, square, saw-tooth and step functions of target force. The performance of outer loop controller also shows significant improvement in terms of body acceleration, body displacement and tire displacement, and spring deflection as compared to the passive suspension system